Different levels of physical activity and depression symptoms among older adults from 18 countries: a population-based study from the Survey of Health, Ageing and Retirement in Europe (SHARE) - Marques, Adilson (2020)
Objective: Analyse the relationship between different levels of physical activity (PA) and depression symptoms in a representative sample of European older adults. Methods: Data on PA, depression symptoms and sociodemographic variables from 64688 (28015 men) older adults participating in SHARE wave 6 was collected through a face-to-face interview. The EURO-D 12-item scale was administered for depression symptoms. Participants reported the frequency they engaged in moderate-intensity PA (MPA) and vigorous-intensity PA (VPA). Results: Men and women engaging in MPA and VPA once or more than once a week had less depression symptoms than those who engage less than once a week. MPA and VPA once or more than once a week were inversely associated with the depression symptoms score. Furthermore, engaging in MPA and VPA decreased the odds of depression (cut-off point of ≥4 depression symptoms) compared to engaging in PA less than once a week. Conclusions: Policies for promoting mental health should include PA for the prevention or treatment of depression symptoms. PA presents physical and psychological benefits and can be used as an overall health-promoting strategy, facing numerous problems at a time.